The Noctuinae (Lepidoptera: Noctuidae) of Great Smoky Mountains National Park, U.S.A. - Pogue, Michael G. (Zootaxa, 2006)
Forty-eight species of Noctuinae are recorded from Great Smoky Mountains National Park, Tennessee and North Carolina, U.S.A., with 17 species in the tribe Agrotini and 31 species in the tribe Noctuini. Images of adults, description/diagnosis, flight period, collected localities, abundance, elevational range, general distribution, and larval hosts are presented for each species. The greatest diversity of Noctuinae species (n=29) was recorded from four combined localities along Big Cove Road, Swain Co., North Carolina.